2009
DOI: 10.1097/qai.0b013e3181a267e4
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the HIV Epidemic in the Dominican Republic: A Prevention Success Story in the Caribbean?

Abstract: As in several other developing countries that have succeeded in slowing HIV transmission, HIV reductions in the DR seem mainly due to changes in sexual behavior, particularly increased condom use, especially for sex work, and partner reduction in men. Similarly favorable HIV declines and reported behavior change have occurred in some other Caribbean countries, including neighboring Haiti. However, of concern is that anal sex, both male-male and heterosexual, remains a taboo yet apparently common practice large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 23 publications
3
63
0
Order By: Relevance
“…However, a recent review of epidemiological and behavioural data in the Dominican Republic concluded that the notable declines in HIV prevalence reported in that country were likely to be due to changes in sexual behaviour, including increased condom use and partner reduction, although the study also highlighted high levels of HIV infection among men who have sex with men (Halperin et al, 2009). …”
Section: Prisonersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent review of epidemiological and behavioural data in the Dominican Republic concluded that the notable declines in HIV prevalence reported in that country were likely to be due to changes in sexual behaviour, including increased condom use and partner reduction, although the study also highlighted high levels of HIV infection among men who have sex with men (Halperin et al, 2009). …”
Section: Prisonersmentioning
confidence: 99%
“…In particular, signs suggest that the drop in HIV prevalence in that country ( Figure 16) may be related to increased condom use and a reduction in multiple partnerships among men (Halperin et al, 2009). …”
Section: Heterosexual Transmissionmentioning
confidence: 99%
“…MSM in Africa are a highly vulnerable population at risk for HIV infection, in spite of this, the Africa region has documented limited HIV and STDs data on MSM, largely due to stigmatization of homosexual behaviour in the population (Smith et al, 2009). After Asia and sub-Saharan Africa, the region most impacted by HIV infection is Latin America where high rates HIV prevalence have been documented among MSM with no evidence of significant decrease (Halperin et al, 2009). …”
Section: The Current Scenario In Developing / Transitional Countriesmentioning
confidence: 99%
“…In addition, because of poverty and the poor quality of life in HT, many Haitians cross the border into the DR every year. 4,25 In the absence of close virological monitoring, drug resistance mutations may selectively expand, rekindling viral evolution. Furthermore, although in the DR the rate of new infection fell by 73% (adults 15-49 years) and there are 61% fewer people dying from AIDS-related causes, routine surveillance of the genetic diversity of HIV-1B is necessary in order to initiate public health efforts.…”
Section: Figmentioning
confidence: 99%
“…29 Interestingly, during the same period, the HIV prevalence among pregnant women (15-24 years old), female sex workers (FSWs), and the general population presented a similar decreasing pattern. 30 Similarly, the growth rates of syphilis and gonorrhea slowed in the late 1990s, 25 which should be evidence of the effectiveness of the viral control effort.…”
mentioning
confidence: 99%